Lessons from experimental MANET research - Tschudin, Christian; Gunningberg, Per; Lundgren, Henrik; Nordström, Erik (Ad hoc networks, 2005)
After almost a decade of research into ad hoc networking, MANET technology has not yet affected our way of using wireless networks. In this paper we discuss lessons to draw and back them with experiences from our experimental work. We find that simulations have to be complemented to a much higher degree by real-world experiments, that there is a lack of mature implementations and integration and that efforts should be focused on more realistic settings inside the “ad hoc horizon” where decent network services still can be provided.